KRISTOLOGI DALAM PANDANGAN RATZINGER DAN TOM JACOBS - Romas, Romanus (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
In this paper, the author wants to make a kind of comparison about the viewsof the theologians Tom Jacobs and Joseph Ratzinger. The two theologiansâopinions are presented in a discourse, and at the end of this discourse, theauthor responds to develop a contextual theology. For the author, the twotheologians have some similarities and a number of points of difference thatcontribute to the richness of the Churchâs Christological reflection in order toheed sacred scriptures and traditions. Although the tension is found betweenfaithful to Scripture and Tradition, the author does not want to give a biasedopinion.